Applications of lipidomics by mass spectrometry in the search for molecular alterations in patients diagnosed with COVID-19 - Rodrigues Chaves, Andréa; Ivo de Oliveira Júnior, Charles; Alves Bernardo, Ricardo (Seven Editora, 2023)
Lipids are responsible for energy reserve, and vitamin absorption, besides being structural and functional components of biomembranes and signaling mediators. Due to the pandemic caused by the dissemination of the SARS-CoV-2 virus, recent researchers have sought to correlate changes in lipid metabolism in different biological matrices, including plasma, tracheobronchial secretions, and nasopharyngeal/oropharyngeal fluids. However, the collection/obtaining of these samples uses invasive protocols, which generates discomfort in patients, being desirable the search for alternative analytical methodologies that use samples collected in a non-invasive way, such as saliva. Because of this, this chapter aims to describe the application of lipidomics by ultra-high-resolution mass spectrometry to assess molecular changes in the spittle of patients diagnosed with COVID-19.DOI: https://doi.org/10.56238/devopinterscie-120